2014
DOI: 10.1136/bcr-2014-205229
|View full text |Cite
|
Sign up to set email alerts
|

The curious case of free-floating pelvic cysts

Abstract: The case of a healthy 33-year-old woman who underwent an elective caesarean section with incidental finding of small free-floating cysts within the pelvic peritoneum is presented. Gross examination could not identify the specimens. Histopathological investigation was necessary to classify the specimens as benign mesothelial cysts. The patient had no medical or surgical history and no other risk factors. The presented case is particularly interesting as the cysts were non-adherent to any pelvic or abdominal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…In contrast, the present cases showed negative reactions for calretinin in the nucleus. In addition, the smooth muscle layers in the stroma were revealed in the present cases, but mesothelioma commonly lacks them [21,29]. Furthermore, almost the previously reported chicken mesotheliomas were associated with tumorigenic ALV infections [5,7,13], but the present cases might be spontaneous tumors without ALV infections.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…In contrast, the present cases showed negative reactions for calretinin in the nucleus. In addition, the smooth muscle layers in the stroma were revealed in the present cases, but mesothelioma commonly lacks them [21,29]. Furthermore, almost the previously reported chicken mesotheliomas were associated with tumorigenic ALV infections [5,7,13], but the present cases might be spontaneous tumors without ALV infections.…”
mentioning
confidence: 50%
“…On the other hand, the present cases developed the multicystic lesion that was different from the previously reported avian mesotheliomas. The present cases morphologically resembled human benign multicystic peritoneal mesothelioma (BMPM) which is a rare tumor developing during reproductive age [9,14,15,21,29]. In BMPM, the neoplastic cells are positive for cytokeratin, vimentin, calretinin and WT-1, and occasionally positive for PR or/and ER [14,15,22,25,28].…”
mentioning
confidence: 67%
“…Though less likely, traumatic hemoperitoneum with a free-floating mass can also be due to rupture of a cystic teratoma (this case report also lacks a positive seat belt sign) [ 13 ]. Other possible etiologies of a free-floating intraperitoneal mass in women can include an ovary, gallbladder, or mesothelial cyst [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of MBM during pregnancy has been reported in five individual patients so far. In three patients, these cysts have been found incidentally at the time of full term Caesarean sections [ 14 , 15 , 17 ]. These patients remained asymptomatic and the pregnancies proceeded uneventfully.…”
Section: Discussionmentioning
confidence: 99%
“…Though this condition predominantly affects women in reproductive age, not a lot is known about its course and management in pregnancy. On review of literature, we found only five reported cases of MBM complicating pregnancy [ 13 17 ]. In four of them, MBM was found as an asymptomatic or incidental diagnosis and the fifth case was treated with termination of pregnancy and tamoxifen.…”
Section: Introductionmentioning
confidence: 99%